The Role of Lung Function Testing in Newborn Infants With Congenital Thoracic Arterial Anomalies - Columbo, Claudia; Landolfo, Francesca; De Rose, Domenico Umberto; Massolo, Anna Claudia; Secinaro, Aurelio; Santangelo, Teresa Pia; Trozzi, Marilena; Campanale, Cosimo Marco; Toscano, Alessandra; Capolupo, Irma; Bagolan, Pietro; Dotta, Andrea (Frontiers in Pediatrics, 2021)
Introduction: Congenital thoracic arterial anomalies (CTAA) such as complete or incomplete vascular rings, pulmonary artery sling and innominate artery compression syndrome, may cause severe tracheomalacia and upper airway obstruction. An obstructive ventilatory pattern at lung function testing (LFT) has been suggested in the presence of CTAA. The severity of obstruction may be evaluated by LFT. Little is known about the use of LFT in newborn infants with CTAA. The aim of our study is to evaluate the role of LFT in CTAA diagnosis. Methods: This is a retrospective study, conducted between February 2016 and July 2020. All CTAA cases who performed LFT preoperatively were considered for inclusion. Tidal volume (Vt), respiratory rate (RR) and the ratio of time to reach the peak tidal expiratory flow over total expiratory time (tPTEF/Te) were assessed and compared to existing normative data. Demographics and CTAA characteristics were also collected. Results: 30 cases were included. All infants with CTAA showed a significant reduced Vt and tPTEF/tE, compared to existing normative data suggesting an obstructive pattern. No significant differences were found for LFT between cases with a tracheal obstruction <50% compared to those with tracheal obstruction ≥ 50%, nor between cases with and without symptoms. Sixteen infants (53.3%) had respiratory symptoms related to CTAA. Of these, only two cases had also dysphagia. Conclusion: LFT values were significantly reduced in cases with CTAA before surgery. LFT represents a potential feasible and non-invasive useful tool to guide diagnosis in the suspect of CTAA.